Empowering Wedding Photographers through Penta-helix Approach - Anwar, Ardy; Fiandra, Yosa; Budiman, Arief (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Wedding photography is a field of photography that has immense potential for development. However, to produce high-quality wedding photography, it requires a solid foundation, especially in terms of incorporating messages or stories into photography and wedding photography business. This community service activity aims to improve the basic competencies of wedding photographers, especially in terms of incorporating messages or stories into photography and wedding photography business. This community service activity was conducted by providing training and workshops on wedding photography to photography communities. The training and workshops were conducted with the Penta helix principle, which is a collaboration between Telkom University, DOSS Bandung, the Snapshot community, the DISBUDPAR of Bandung Regency, and APFI. The results of this community service activity showed that there was an improvement in the quality of photography among participants, especially in terms of lighting and camera angles.